Ebola virus disease and critical illness. Issue 1 (December 2016) - Leligdowicz, Aleksandra; Fischer, William; Uyeki, Timothy; Fletcher, Thomas; Adhikari, Neill; Portella, Gina; Lamontagne, Francois; Clement, Christophe; Jacob, Shevin; Rubinson, Lewis; Vanderschuren, Abel; Hajek, Jan; et al.
Abstract As of 20 May 2016 there have been 28, 646 cases and 11, 323 deaths resulting from the West African Ebola virus disease (EVD) outbreak reported to the World Health Organization. There continue to be sporadic flare-ups of EVD cases in West Africa. EVD presentation is nonspecific and characterized initially by onset of fatigue, myalgias, arthralgias, headache, and fever; this is followed several days later by anorexia, nausea, vomiting, diarrhea, and abdominal pain. Anorexia and gastrointestinal losses lead to dehydration, electrolyte abnormalities, and metabolic acidosis, and, in some patients, acute kidney injury. Hypoxia and ventilation failure occurs most often with severe illness and may be exacerbated by substantial fluid requirements for intravascular volume repletion and some degree of systemic capillary leak. Although minor bleeding manifestations are common, hypovolemic and septic shock complicated by multisystem organ dysfunction appear the most frequent causes of death. Males and females have been equally affected, with children (0–14 years of age) accounting for 19 %, young adults (15–44 years) 58 %, and older adults (≥45 years) 23 % of reported cases. While the current case fatality proportion in West Africa is approximately 40 %, it has varied substantially over time (highest near the outbreak onset) according to available resources (40–90 % mortality in West Africa compared to under 20 % in Western Europe and the USA), by age (near universal among neonates and high among older adults), and by Ebola viral load at admission. While there is no Ebola virus-specific therapy proven to be effective in clinical trials, mortality has been dramatically lower among EVD patients managed with supportive intensive care in highly resourced settings, allowing for the avoidance of hypovolemia, correction of electrolyte and metabolic abnormalities, and the provision of oxygen, ventilation, vasopressors, and dialysis when indicated. This experience emphasizes that, in addition to evaluating specific medical treatments, improving the global capacity to provide supportive critical care to patients with EVD may be the greatest opportunity to improve patient outcomes.